Discrepancies between standardised testing and teacher judgements in an Australian primary school context - Carmichael, Colin (My University, 2015)
This study compares the judgments that teachers make on their students' mathematics achievement with results taken from Australia's National Assessment Program: Literacy and Numeracy (NAPLAN). Using a sample of 2144 students, drawn from the Longitudinal Study of Australian Children (LSAC), the study develops two regression models: one with teacher ratings of achievement as the outcome variable, and the other with NAPLAN numeracy results as the outcome. A number of individual and environmental factors are then regressed onto these outcome variables, and the magnitudes of their effects are compared. The results indicate a consistency between teachers’ judgements and NAPLAN test results, except for students with special needs, where a significant discrepancy exists. Implications of these results are discussed.
Mathematics Teacher Education and Development
Keywords: Child Development; Education and Training -- Primary; Children -- Outcomes; Education and Training -- Literacy and numeracy; Childhood and child development; Learning, education and training; Child Development; Children; Education and Training; Literacy and numeracy; Primary; Outcomes; Learning, education and training; Childhood and child development